Fifty Golden Years of IFFCO transforming Indiaâ€™s agriculture and rural lives - Awasthi, U S (Indian Farming, 2017)
India has to grow more and more food from less land, water and energy. Fertilizer will continue to play important role to boost agricultural production. IFFCO is making allÂ efforts for optimum, efficient and more profitable use of fertilizers and also to keep the cost of production low. The government is expected to extend generous support for longterm economic and strategic interest of domestic fertilizer industry on the lines and patterns of â€˜Make in Indiaâ€™ initiative. The emerging problems of multinutrient deficiencies are responsible for deterioration in the soil health and as such attainable potentials of high yielding cultivars are not being exploited. India is also facing serious problem of mal nutrition. For the people to get safe and nutritious food diversification of agriculture would ensure the quantity and the quality of the agricultural produce. The foodgrains, fodder, feed, vegetables and fruits grown on impoverished soils are bound to be low in nutrient contents which in turn influence human and animal health. Optimum, balanced and efficient use of fertilizers to correct the existing nutrient deficiencies on the principle of integrated nutrient supply would be essential and inevitable. â€œFeed the Soil to Feed the Crops to Feed the Worldâ€ should be the motto of the day to sustain food, nutrition and environment security.